Synthesis of polyallenoates through copper-mediated cross-coupling of dialkynes and bis-α-diazoesters. Issue 24 (3rd March 2022) - Yu, Lefei; Zhou, Qi; Gao, Yunpeng; Fu, Zihao; Xiao, Yiyang; Li, Zi-Chen; Wang, Jianbo
Abstract : Cross-coupling reaction of terminal alkynes and diazoesters has been applied in polymerization by using a copper/chiral guanidinium salt system, affording polyallenoates in high yields and in an enantioselective manner. Abstract : The copper-catalyzed cross-coupling of alkynes and α-diazoesters has been applied in the synthesis of polyallenoates for the first time. The polymerization tolerated various functional groups and afforded the polyallenoates with high molecular weight. With chiral guanidinium bromide as a ligand, the axial chirality of the allene moiety could be generated with high enantioselectivity during the polymerization process.